Computational investigation of α-SiO2 surfaces as a support for Pd. Issue 8 (8th February 2023) - Lombard, C. J.; van Sittert, C. G. C. E.; Mugo, J. N.; Perry, C.; Willock, D. J.
Abstract : Identifying the adsorption sites for Pd on the surfaces of α-SiO2 . Abstract : The properties of a supported metal catalyst depend crucially on the interaction between the active metal and the support. A case in point is Pd supported on silica, Pd/SiO2, which is widely used in oxidation catalysis. There is a need for a broad range of computational models that describe the interaction of Pd with silica surfaces so that active site models can be proposed and tested. In this work, we create well-defined, reproducible, periodic models of SiO2 surfaces and investigate their interaction with Pd using dispersion-corrected DFT. We use crystalline α-SiO2 as a useful starting point for creating and estimating the adsorption properties of metals on SiO2 surfaces, which can represent the specific isolated functional groups present on more complex amorphous silica surfaces. We have modelled α-SiO2 (001), (100) and (101) surfaces containing isolated siloxane and silanol functional groups and estimated their affinity towards the adsorption of Pd atoms regarding an isolated gaseous Pd atom and the fcc Pd solid. This provides additional information on the ease with which Pd can be dispersed on the surfaces in question. From our model, we characterise the surface energies of the α-SiO2 ( hkl ) surfaces and calculate the geometries of the Pd1 /α-SiO2 ( hkl ) adsorption site on each surface. We estimate that Pd1 (g) will prefer to adsorb close to strained four-membered siloxane rings or on a vicinal silanol group of α-SiO2 (101).